2000
DOI: 10.1111/j.1540-8167.2000.tb00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Characteristics of the Atrium in Sinus Node Dysfunction:

Abstract: In patients with SND, atrial refractoriness appears similar to that of control subjects. The most important EP abnormality appears to be local conduction slowing disturbances, with prolonged basal and postextrastimuli atriograms, responsible for a lower vulnerability index. This could explain, at least in part, the tendency of patients with SND to develop AF during their natural history. Normality of atrial refractoriness, in contrast to atrial conduction disorders, might explain why atrial pacing shows a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…12,13 These abnormalities have been observed during both sinus rhythm and atrial pacing, with a suggestion that patients who had associated AF had a wider distribution of abnormal atrial findings. De Sisti et al 14 retrospectively reviewed patients with SND who had electrophysiological assessment and found no change in ERP at the high RA at a CL of 600 ms but significant increase in electrogram duration both during the drive CL and extrastimulus compared with controls. However, the control group in that study was not age-matched and included patients with syncope or other conduction abnormalities.…”
Section: Previous Studies Of Atrial Abnormalities In Sndmentioning
confidence: 99%
“…12,13 These abnormalities have been observed during both sinus rhythm and atrial pacing, with a suggestion that patients who had associated AF had a wider distribution of abnormal atrial findings. De Sisti et al 14 retrospectively reviewed patients with SND who had electrophysiological assessment and found no change in ERP at the high RA at a CL of 600 ms but significant increase in electrogram duration both during the drive CL and extrastimulus compared with controls. However, the control group in that study was not age-matched and included patients with syncope or other conduction abnormalities.…”
Section: Previous Studies Of Atrial Abnormalities In Sndmentioning
confidence: 99%
“…Although several parameters, such as the atrial refractory period, fragmented atrial activity, atrial conduction delay, repetitive atrial firing, wavelength index, and inducibility of atrial fibrillation have been proposed as indices of atrial vulnerability, it remains uncertain whether these indices also represent inherent electrophysiologic properties in elderly people without atrial fibrillation. [5][6][7][10][11][12][13][14][15][16][17] The percent maximum atrial fragmentation has been reported to reflect prolongation of the atrial electrogram, the presence of a conduction abnormality, or the occurrence of atrial fibrillation. 13) In this study, the percent maximum atrial fragmentation was greater in patients with inducible atrial fibrillation than in those without inducible atrial fibrillation, which is concordant with previous reports.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…7,[10][11][12][13] 2) Right atrial effective refractory period: Right atrial effective refractory period was defined as "the longest S1-S2 interval that does not provoke A2 in the high right atrium". 10,[13][14][15] 3) Wavelength index: Wavelength index was defined as "the ratio of effective refractory period / maximum width of A2". 10,[13][14][15][16] …”
Section: ) Percent Maximum Atrial Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the type of SND might predict the degree of atrial remodeling and predict the outcome after RFCA of AF (7). In contrast, De Sisti et al (8) found that the right atrial effective refractory period was not changed significantly in the enrolled patients with SND (8). However, the AERP measurements were performed only at a single site and the control group was not age-matched in their study.…”
mentioning
confidence: 85%